Catalytic C-F bond activation of geminal difluorocyclopropanes by nickel(I) complexes via a radical mechanism - Wenz, Jan; Rettenmeier, Christoph Alexander; Wadepohl, Hubert; Gade, Lutz H. (Chemical communications, 2016)
Nickel(II) fluorido complexes bearing NNN-pincer ligands were found to be catalysts in the hydrodefluorination of geminal difluorocyclopropanes which undergo ring-opening to form the corresponding monofluoroalkenes in good yield and high Z-selectivities. Evidence for a radical based mechanism involving nickel(I) and nickel hydrido complexes as key intermediates was obtained in the corresponding stoichiometric reactions.
Gesehen am 26.06.2020
First published 13 Nov 2015